Information Systems of Official Trips at General Election Commission Office (KPU) - Bayu Rianto; Fitri Yunita; Muhammad Amin; Rahma Rahma (Universitas Negeri Padang, 2021)
The General Election Commission (KPU) of Indragiri Hilir Regency has not had a particular application that helps financial staff make a warrant for an official trip. Recently, it has been made by using Microsoft Word. Therefore, researchers create a system to facilitate it easier. This study uses the waterfall method in developing its system, which includes the stages of needs analysis, data collection, application development, testing, and implementation. The data collection was done by utilizing observation, interviews, and literature studies. The modeling system used is UML modeling (Unified Modeling Language) web-based with the programming language PHP (Hypertext Preprocessor) and MySQL database. This study's results can make it more straightforward for financial staff to make a warrant for an official trip. It makes it easier to find information related to past official travel if needed.